Twelfth mode on-demand band notch UWB antenna for underlay cognitive radio - Laith Wajeeh Abdullah; Musa H. Wali; Adheed H. Saloomi (Institute of Advanced Engineering and Science, 2021)
A wide-slot ultra-wideband (UWB) antenna with on-demand band rejection characteristics that can serve underlay cognitive radio is presented in this paper. This antenna is designed to work in twelve operation modes; one to cover the whole UWB while each of the rest modes excludes one or more of the ranges that are allocated for Worldwide Interoperability for Microwave Access (WiMax), C-band, wireless local area network (WLAN), X-band and International Telecommunication Union (ITU) in a single, dual, triple, quad or penta band rejection state. A spiral shape slot in the patch and three slots mainly based on half-circular structures in the ground plane are the means to create the desired frequency notches. A positive-intrinsic-negative (PIN) diode across each of these slots is used to enable/disable band(s) rejection process. Configuration of the proposed antenna to the desired mode of operation is decided by the state of its four PIN diodes. This work is simulated by computer simulation technology (CST) v.10. It’s S11, voltage-standing-wave-ratio (VSWR) and realized gain results when combined with antenna's 25x25x0.8 mm3 compact size and the large number of modes and states, all ensure its capability to eliminate or reduce the interference within the targeted bands and hence being suitable for the applications of underlay cognitive radio.